DIMENSI SUFISTIK DANARTO DALAM CERPEN âO, JIWA YANG EDANâ: TINJAUAN SEMIOTIK - Nugraheni, Sekar; Sufanti, Main (Kajian Linguistik dan Sastra, 2007)
The purpose of this research is to describe the dimension of sufistic in of shortstory âO, Jiwa yang Edanâ masterpieces of Danarto with semiotic evaluation. Theresult of the sufistic dimension in a short story âO, Jiwa yang Edanâ is on thetasawuf, terminology, understanding and hierarchy in tasawuf. At tasawuf hierarchythere are four steps which much be passed by that: (1) syariâat, (2) tarikat, (3)hakikat, and (4) makrifat. In the short story of âO, Jiwa yang Edanâ the four stepsstarted from the tarikat described by leaving of enjoyment world. While the hakikatdescribed that any creature will go home to the God. Makrifat is if someone becometo recognize the reality of Allah. The understanding of tasawuf used by theauthor of short story is wahdatul syuhud.